Clinical acceptability and ease of use of a safety IV catheter system (2012)
Objective: Occupational risk of transmission of bloodborne pathogens represents a major challenge in prevention. Even though preventive recommendations to avoid needlestick injuries among healthcare workers include the use of needle protective devices, its use in developing countries is not a standard practice. This study aimed to measure, on experienced nurses, perception of performance characteristics and activation of the safety feature of a safety closed IV catheter system (BD Pegasus*), called catheter P, versus a non-safety device (BD Intima II†) called catheter I in healthy volunteers. Method: Fifty-two nurses and 205 healthy volunteers participated in a prospective, randomized, controlled study in a simulated setting. Each nurse performed two insertions of each catheter (one in each forearm) in four study volunteers; the order of insertions was randomly assigned. Statistical analyses were performed to compare the performance of the two catheters regarding Overall Perception of Clinical Acceptability and Ease of Use. Results: Overall acceptance of the device performance characteristics was 90 or more. In all cases, catheter P performed at least as well as catheter I. There were no differences in the insertion success rate between the two devices (93.7 vs. 96.2). Activation of the safety feature of catheter P occurred 99.4. Subjects' perception of pain was similar for both devices. Overall perception of clinical acceptability and ease of use were judged better for catheter P than for catheter I (p=0.006, and p less than 0.001 respectively). All clinicians strongly agreed that catheter P would protect them from needle stick injuries. Conclusions: Despite the study limitations, mainly its artificial setting and its inability to blind, the results indicate that the Safety Closed IV Catheter System with its safety feature represents a good alternative for IV catheter insertions that can help reduce the incidence of stick injuries in health care workers. © 2012 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.